Advances in hydrogel-based solar-driven interfacial evaporation systems: The pivotal factors and design strategies from photothermal engineering to energy management - Huang, Xin; Cui, Yongqian; Kumar, Nitish; Sun, Jinhua; Lin, Yuhan; Nuraje, Nurxat; Wang, Chuanyi (Separation and purification technology, 2025)
Hydrogels for interfacial solar-driven seawater desalination. [Display omitted] •A novel perspective is offered on the dynamic mass transfer processes in hydrogel-based solar-driven interface evaporation systems, emphasizing electronic transition mechanisms and proposing a collaborative “ photon absorption-carrier relaxation-thermal diffusion ” energy conversion model.•Supported by density functional theory calculations from existing literature, this review explores the mass and heat transfer behaviors of noble metal plasmonic materials, narrow-bandgap semiconductors, and π-conjugated polymers in HSE applications.•By establishing a mapping framework between the inherent properties of photothermal materials and evaporator performance, we critically analyze the local energy dissipation, carrier recombination center formation and salt crystallization effects of existing HSE systems.•Building upon current research advances, we propose multiple crosslinking strategies, energy band engineering, defect engineering, and nanostructure designs to enhance hydrogel evaporation performance and surpass evaporation limits. As the most promising sustainable alternative to traditional seawater desalination technologies, hydrogel-based solar-driven interface evaporation (HSE) systems are subject to the persistent challenges of evaporation performance and mass transfer efficiency. However, the current review neither summarizes the mechanistic differences of photothermal materials between hydrogel and non-hydrogel systems, nor reveals the characteristics of relaxation kinetics during non-equilibrium energy transfer. To fill this gap, this review surveys recent advances in photothermal materials for HSE systems. Moreover, based on photothermal engineering design, a collaborative “photon absorption-carrier relaxation-thermal diffusion” energy conversion model is introduced. Supported by density functional theory calculations, this model elucidates the mass and heat transfer behaviors of noble metal plasmonic materials, narrow-bandgap semiconductors, and π-conjugated polymers in HSE applications. By establishing a mapping framework between the inherent properties of photothermal materials and evaporator performance, the local energy dissipation, carrier recombination center formation and salt crystallization effects of existing evaporation systems are critically analyzed. Furthermore, strategies including material design, defect engineering and biomimetic structure to achieve full spectrum utilization are proposed. The theoretical framework and engineering guidelines presented in this review are intended to promote a scientific understanding of HSE systems while demonstrating the immense potential of HSE systems in advancing sustainable desalination technologies.